Comparative Performance Analysis of TCP Congestion Control Algorithms over IPv4 and IPv6 - Lima, Vitor Reiel M.; Callado, Arthur C.; Bonfim, Michel S.; Coutinho, Emanuel F. (Anais do Workshop em Desempenho de Sistemas Computacionais e de Comunicação (WPerformance); 2026: Anais do XXV Workshop em Desempenho de Sistemas Computacionais e de Comunicação, 2026)
TCP, the main protocol for reliable data transport on the internet, has undergone numerous modifications over the years, resulting in various versions with specific characteristics for congestion control. Given the rapid growth of the internet and the gradual transition from IPv4 to IPv6, understanding the operation and performance of these versions in different network environments is essential. This study provides a comparative analysis of different TCP versions, which are embedded within the network stack and adapt to hardware buffer constraints, in scenarios operating with either IPv4 or IPv6. The experiments emulate adverse network conditions, including delay, packet loss, and congestion, to evaluate performance metrics during scenario execution. The results highlight the most efficient TCP versions under common network conditions and offer insights into their behavior when configured to operate with IPv4 or IPv6.